Ukraine : Social Safety Nets and Poverty, Volume 1 - World Bank (Washington, DC, 2013)
The report is intended to determine the appropriateness of the social protection system in meeting the needs of the poor in Ukraine, and what are the changes which can be instituted to improve such system. To this end, the report presents the poverty measurement in the country, assesses current social programs, and suggests a framework for system redesign. In particular, it points at the challenge of a transition economy, in realizing that poverty does appear even among the employed population, while childhood poverty does indeed affect the future of a nation. The study presents the survey methodology, based on a household survey, measures of income and expenditure, and of inequality, examining the poverty line through a multivariate analysis of poverty risks in the country, including housing subsidies, energy arrears, in addition to war entitlements and privileges. It finds that the Ukrainian social support system could address social needs well, as it has sufficient resources to do so, though currently, it does so poorly. Thus resource allocation needs to be improved, by targeting categorical benefits, testing asset and income potential, as well as using indicators to substitute for the direct measurement of income. An additional quantitative analysis will be required to better plan management, and effective evaluation, in addition to a system redesign to reduce funding for poorly targeted programs, while increasing social funding at large. A strategy is proposed to phase-in a social assistance reform over a four-year period, supported by the Bank.